Coronary arteries bypass grafting in dialysis dependent end stage renal disease, results and outcome - Altaani, Haitham; Alfawares, Safwan; Alsharoo, Saker; Obeidate, Mahmoud; Maloof, Khaled; Jabber, Saad (International Journal of Research in Medical Sciences, 2016)
Background: The objective is to assess the results and outcome of patients with dialysis dependent end stage renal failure who underwent coronary artery bypass grafting. Methods: In this retrospective study we analyzed the medical records of dialysis dependent end stage renal failure patients who underwent isolated coronary artery bypass grafting from January 2008 till December 2012 at queen alia heart institute. The total number of patients were 62 out of 6522 (0.95%). 42 of them were male (68%), the average age was 48±12 year, the duration of dialysis was 17±7 months. The medical profile of the patients, renal condition and duration of dialysis were analyzed. Preoperative cardiac condition and risk factors were also analyzed. Operative variables and postoperative results including mortality and post-operative renal and cardiac related complications were also analyzed. Results: Total in hospital mortality was 5 (8%), the cause of mortality was renal failure related causes in 2 patients, sepsis in 2 patients, cardiac causes in one patient. Average time for extubation, ICU stay and hospital stay was 9±2.3 hours, 27±7 hours and 7 days respectively. The average amount of blood loss postoperatively was 450±55 ml; five patients (8%) were resent to the operating theatre for exploration resternotomy because of bleeding. The average creatinine level 6.5±1.5 mg/dl. Six patients need dialysis in the first 24 hours of the operation (9.7%), most patients were returned to the usual protocol of dialysis, which was in average of 3 times per week. Conclusions: Coronary artery bypass grafting is the standard treatment in patient of end stage renal disease with coronary artery disease. Surgery is the ideal treatment in three vessel and left main disease according to SYNTAX trial. Those patients are high risk candidate for surgery, but proper preoperative, intraoperative and postoperative management decrease the risk and make the procedure safe.